2011
DOI: 10.1007/s11060-011-0736-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid stimulates leptomeningeal and meningioma cell proliferation and activation of STAT3

Abstract: The role of cerebrospinal fluid (CSF) in the pathogenesis of meningiomas is unknown. Cell cultures from three human leptomeninges, five WHO grade I and seven grade II meningiomas were treated with remnant CSF from 22 patients with no central nervous system disease and normal cell indices. Cells were evaluated by CyQUANT for DNA synthesis/cell proliferation and by western blots for phosphorylation/activation of growth regulatory pathways activated in meningiomas including JAK1-STAT3, MEK1-p44/42MAPK, Akt-mTOR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…These findings are consistent with the known effects of STAT3 activation on cell proliferation, apoptosis and angiogenesis (20,(23)(24)(25). In a previous study, we demonstrated that cerebrospinal fluid stimulated the phosphorylation/activation of STAT3 in grade I/II primary meningioma cell cultures (6). Furthermore, our previous study revealed that the mitogenic effects of cerebrospinal fluid on WHO grade I and II meningioma cells appear to be exerted, in part, via the activation of STAT3 (6).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings are consistent with the known effects of STAT3 activation on cell proliferation, apoptosis and angiogenesis (20,(23)(24)(25). In a previous study, we demonstrated that cerebrospinal fluid stimulated the phosphorylation/activation of STAT3 in grade I/II primary meningioma cell cultures (6). Furthermore, our previous study revealed that the mitogenic effects of cerebrospinal fluid on WHO grade I and II meningioma cells appear to be exerted, in part, via the activation of STAT3 (6).…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, we demonstrated that cerebrospinal fluid stimulated the phosphorylation/activation of STAT3 in grade I/II primary meningioma cell cultures (6). Furthermore, our previous study revealed that the mitogenic effects of cerebrospinal fluid on WHO grade I and II meningioma cells appear to be exerted, in part, via the activation of STAT3 (6). In addition, we have identified activation of STAT3 in grade I and II meningiomas, with increased phosphorylation/activation in grade II tumors (9).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Human cerebrospinal fluid from patients without neurological disease. As meningiomas are bathed in cerebrospinal fluid, which has been demonstrated to affect meningioma cell proliferation (13), its effects on APOBEC3B were evaluated in the current study. Remnant, discarded lumbar cerebrospinal fluid was collected at the University of Rochester Medical Center and sent to the Department of Pathology between March 2009 and September 2012.…”
Section: Introductionmentioning
confidence: 99%